PENGARUH KEEFEKTIFAN PENGENDALIAN INTERNAL, PERILAKU TIDAK ETIS DAN KETAATAN ATURAN AKUNTANSI TERHADAP FRAUD MELALUI KEPUASAN KERJA (STUDI EMPIRIS PADA ORGANISASI PERANGKAT DAERAH KABUPATEN KAMPAR) - Noprial Valenra Maksyur; Taufeni Taufik; Azwir Nasir (Jurnal Ekonomi, 2018)
The purpose of this study was to examine the effect of internal control effectiveness, unethical behavior and compliance with accounting rules on fraud through job satisfaction in Kampar District Offices. This research was conducted on 31 regional device organizations in Kampar District. Respondents used in this study amounted to 93, data returned and can be processed as many as 88 respondents. The independent variables in this study are the effectiveness of internal control, unethical behavior and compliance with accounting rules. Dependent variable is fraud. Intervening variables are job satisfaction. Data collected from 88 respondents was further analyzed with the help of WarpPLS version 5.0 software. The results of the study prove that the effectiveness of internal control, unethical behavior and adherence to accounting rules affect fraud, as well as variable job satisfaction can mediate the relationship between variables of internal control effectiveness, unethical behavior, and compliance with accounting rules.